ALIH KODE DAN CAMPUR KODE BAHASA GAYO-INDONESIA DALAM INTERAKSI JUAL BELI DI PASAR TRADISIONAL TAKENGON - Sari, Gustina; Alfi Syahrin; Wirdatul Isnani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the bilingual condition of the community at Paya Ilang Market, Takengon, where Gayo and Indonesian are used interchangeably in daily communication. It aims to describe the forms of code-switching and code-mixing, as well as the factors causing them, in the interactions between sellers and buyers at Paya Ilang Market. A qualitative descriptive method was applied. The data sources were the utterances of sellers and buyers, collected through observation, listening, recording, and note-taking techniques, and analyzed through data reduction, data display, and conclusion drawing. The results show that 19 instances of code-switching and 29 instances of code-mixing were found. The code-switching found was internal, namely the shift between Gayo and Indonesian, occurring mainly across sentences, within a single utterance, and between speakers. The code-mixing found mainly involved the insertion of Gayo particles, words, phrases, and expressions into Indonesian utterances. The factors causing code-switching and code-mixing include the interlocutor, language habits, familiarity, informal situations, and the speakers' ethnolinguistic background. It can be concluded that code-switching and code-mixing at Paya Ilang Market occur naturally in this bilingual community, functioning to ease communication, build familiarity, and adjust to the interlocutor and the situation. This study is expected to contribute to sociolinguistic studies on bilingual communities, particularly regarding code-switching and code-mixing in traditional market interactions. Kata Kunci: alih kode, campur kode, bilingualisme, pasar tradisional, bahasa Gayo